1998
DOI: 10.1143/jjap.37.l1132
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electron Mobility of AlInSb/InAsSb/AlInSb Heterostructures Grown Lattice-Mismatched on GaAs Substrates

Abstract: We have improved the electron mobility of Al x In1-x Sb/InAs y Sb1-y /Al x In1-x Sb heterostructures grown by molecular beam epitaxy. By using Al0.15In0.85Sb as high-resistivity barrier layers and by using InAs y Sb1-y (whose composition was chosen to be lattice-matched wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…InAsSb is a very attractive material for both electrical and optical application because of its high mobility and small energy gap. [1][2][3][4] Its band gap depends on its antimony content and, at an antimony content of approximately 0.65, reaches a minimum of approximately 0.11 eV, which is approximately half the band gap of InSb. Furthermore, its lattice constant is 2.3% smaller than that of InSb.…”
mentioning
confidence: 99%
“…InAsSb is a very attractive material for both electrical and optical application because of its high mobility and small energy gap. [1][2][3][4] Its band gap depends on its antimony content and, at an antimony content of approximately 0.65, reaches a minimum of approximately 0.11 eV, which is approximately half the band gap of InSb. Furthermore, its lattice constant is 2.3% smaller than that of InSb.…”
mentioning
confidence: 99%
“…and was sufficient to prevent parallel conduction in the buffer layer. 6,9 The InAs y Sb 1Ϫy channel thickness, L z , was fixed at 20 nm, enough to accumulate the electrons in the channel. The electron mobility and sheet electron concentration as a function of the As-shutter duty cycle ͑i.e., As content y͒ are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that the Al content of Al x In 1Ϫx Sb must be at least 0.15 to achieve a highly resistive barrier layer. 6 The electron mobility of an Al 0.15 In 0.85 Sb/InSb/Al 0.15 In 0.85 Sb heterostructure ͑InSb thickness: 20 nm͒ was, however, only 2 120 cm 2 V Ϫ1 s Ϫ1 , even though the InSb thickness was below the critical layer thickness ͑CLT͒ of 32 nm. 6,7 To avoid the problem of lattice strain, we grew Al 0.15 In 0.85 Sb/InAs y Sb 1Ϫy /Al 0.15 In 0.85 Sb heterostructures with reduced lattice mismatch and achieved a high electron mobility exceeding 28 000 cm 2 V Ϫ1 s Ϫ1 at RT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation